Nanotechnology and Food: Brief Overview of the Current Scenario. (2015) - Gallocchio, Federica; Belluco, Simone; Ricci, Antonia
Abstract: The rapidly expanding sector of nanotechnologies has applications in every industrial sector. The production of food of animal origin recognizes several possibilities for technological development through the use of nanomaterials, at animal farming, food processing and product storage levels. Direct use of nanomaterials during these production stages, as well as the uptake from the environment, can lead to the presence of such materials in the final product. In this context analytical methods for the detection and characterization of nanomaterials in complex food matrices and toxicological data are strongly needed to assess the risk for consumers.